A CRISPR CASe for high-throughput silencing - Heintze, Jacob; Luft, Christin; Ketteler, Robin (Frontiers in Genetics, 2013)
Manipulation of gene expression on a genome-wide level is one of the most important systematic tools in the post-genome era. Such manipulations have largely been enabled by expression cloning approaches using sequence-verified cDNA libraries, large-scale RNA interference libraries (shRNA or siRNA) and zinc finger nuclease technologies. More recently, the CRISPR (clustered regularly interspaced short palindromic repeats) and CRISPR-associated (Cas)9-mediated gene editing technology has been described that holds great promise for future use of this technology in genomic manipulation. It was suggested that the CRISPR system has the potential to be used in high-throughput, large-scale loss of function screening. Here we discuss some of the challenges in engineering of CRISPR/Cas genomic libraries and some of the aspects that need to be addressed in order to use this technology on a high-throughput scale.